The Effect of Nursing Simulation on the Clinical Judgment of Nursing Care for Patients with Increased Intracranial Pres-sure (IICP) - Ae Ri Jang; Jeong-Eun Moon (Tehran University of Medical Sciences, 2021)
Background: Nursing educators commonly adopt simulations to educate nursing students and evaluate their clinical thinking, clinical reasoning, and clinical judgment. We aimed to determine the effectiveness of established nursing care simulations by evaluating, through video, a select number of nursing students in scenarios that simulate nursing care for Increased Intracranial Pressure (IICP) patients. Methods: The participants were students in their senior year at a nursing college in South Korea in 2018. We adopted a mixed-method design by first conducting a nonequivalent control group pre-test/post-test research design, then analyzing the experimental group's simulation videos. The participants consisted of 38 students in the experimental group and 39 students in the control group, and each group consisted of 9 teams. This study measured the level of anxiety (Cronbach's α=0.780), critical thinking (Cronbach's α=0.895), performance (Cronbach's α=0.927), theoretical knowledge (Cronbach's α=0.970), and analyzed clinical judgments by directly reviewing video from the experimental group. We used a mixed methods appraisal tool (MMAT) version 2018 as its research checklist. Results: Confidence (P=0.000), theoretical knowledge (P=0.000), clinical performance (P=0.017) indicated statistically significant increases in the experimental group. We subsequently identified 10 clinical judgment processes, including "Identify the patient's condition" to "Reassess the condition after symptoms improve" by analyzing the simulation videos. Conclusion: Developing a simulation for nursing care is effective in honing students' clinical judgment and enhancing their theoretical knowledge, confidence, and clinical performance.